Study of badlands in Derveni area (North Peloponnesus, Greece), as climatic change indicators in Quaternary. - Stamatopoulos, L.; Vassilopoulos, A.; Evelpidou, N.; Gkavakou, P. (7th International Conference on Geomorphology, 2009)
The main objectives of this study are to identify, classify and map the badlands area, as well as to identify the underlain soil types and determine the connection between badlands and climatic changes during Quaternary. The area along the southern coast of the Central Corinth graben, near the town of Derveni (North Peloponese) was chosen as a case study, since extended erosion landforms display geomorphological characteristics, typical of badlands. The area is built up by Plio-Quaternary lacustrine clays with intercalations of distal parts of the fan deltas deposits and records an intensive structural elevation from Pliocene until today. The study focuses on the main factors that contributed in the formation and evolution of badlands in the area, with strong emphasis on geological structure, climatic and sea-level changes and human activity, as well as on the interaction of these factors. It concludes in a geomorphological map with the badlands distribution and discusses the impacts on land degradation and the possible actions against further expansion